An Analysis of Uncertainty and Robustness of Waterjet Machine Positioning Vision System - Dziak, D. M.; Jachimczyk, B. S.; Kulesza, W. J. (Elektronika ir Elektrotechnika, 2013)
The paper presents a new Automatic Waterjet Positioning Vision System (AWPVS) and investigates components of workpiece positioning accuracy. The main purpose of AWPVS is to precisely identify the position and rotation of a workpiece placed on a waterjet machine table. Two webcams form a basis for the system, and constitute its characteristics. The proposed algorithm comprises various image processing techniques to assure a required identification precision. To validate the PVS identification quality, synthetic images were applied under various conditions. The analysis ascertains dependence of an object detection rate and accuracy on a size of cropping frame. Experimental results of the proposed PVS prototype prove that a combination of the vision algorithm and webcams is an alternative to dedicated expensive industrial vision systems. The two main components of AWPVS uncertainty, a machine component and PSV component are discerned and estimated. DOI: http://dx.doi.org/10.5755/j01.eee.19.9.5656